Teknik Pengamanan Pesan Pada Citra Digital Dengan Algoritma Einstein Dan End Of File - Destian Rosmawati Lahagu (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
To be able to secure maximum data, we need a method in cryptographic techniques with a combination of steganography techniques. The cryptographic algorithm that can be used to secure data is einstein. This algorithm works by combining each plaintext character with a key character (in this case the length of the key and plaintext must be the same) so as to produce an incomprehensible form (ciphertext). One of the steganographic methods that can be used is end of file (EOF). This method works by inserting the data to be hidden into the image, then extracting it to view the data again. The results of the research conducted by the author, by applying cryptographic techniques and combining them with steganography techniques, obtained a data security system that can secure data optimally.